2021
DOI: 10.1007/s11665-021-06241-x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Mechanical Properties, and Martensitic Transformation in NiTi Shape Memory Alloy Fabricated Using Electron Beam Additive Manufacturing Technique

Abstract: The electron beam additive manufacturing (EBAM) method was applied in order to fabricate rectangular-shaped NiTi component. The process was performed using an electron beam welding system using wire feeder inside the vacuum chamber. NiTi wire containing 50.97 at.% Ni and showing martensitic transformation near room temperature was used. It allowed to obtain a good quality material consisting of columnar grains elongated into the built direction growing directly from the NiTi substrate, which is related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
(11 reference statements)
1
11
0
Order By: Relevance
“…A recent study reporting on PBF-EB/M manufacturing of a Ni-Ti SMA also revealed similar columnar grained microstructures [15]. However, the microstructures shown in other studies focusing on Ni-Ti even feature a higher texture component in the h001idirection [15,16]. Zhou et al [15] comprehensively discussed the microstructural evolution of PBF-EB/M processed Ni-Ti.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…A recent study reporting on PBF-EB/M manufacturing of a Ni-Ti SMA also revealed similar columnar grained microstructures [15]. However, the microstructures shown in other studies focusing on Ni-Ti even feature a higher texture component in the h001idirection [15,16]. Zhou et al [15] comprehensively discussed the microstructural evolution of PBF-EB/M processed Ni-Ti.…”
Section: Resultsmentioning
confidence: 85%
“…Furthermore, the microstructure was found to be different compared to well-known PBF-LB/M manufactured Ni-Ti SMAs [11,15]. Recent studies demonstrate that upon PBF-EB/M of Ni-Ti strongly textured microstructures appear, which can be rationalized by epitaxial solidification [15,16].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Varying the heat input as a function of the built-up wall height makes it possible to control cooling and therefore the solidification rate. However, no approach for forming the desired grain structures is guaranteed, especially in materials inclined to form large columnar grains such as nickel superalloys [30], titanium [31], copper [32], bronze [33], nickel titanium [34,35], etc. In connection with this, finding out the limiting maximum and minimum values of the heat input for deposition of each material is an important task.…”
Section: Introductionmentioning
confidence: 99%